Research on rotary nozzle structure and flow field of the spinneret for centrifugal spinning. Issue 33 (8th April 2021) - Lai, Zilong; Wang, Jiawei; Liu, Kang; Li, Wenhui; Zhang, Zhiming; Chen, Boya
Abstract: High‐speed centrifugal spinning is a novel method of fabricating nanofibers by use of centrifugal force field. The neoteric designs and proper structural parameters of spinning nozzle will change the outlet velocity and velocity distribution uniformity of spinning solution, which could affect the quality of nanofibers. Four different spinning nozzles that can be used for high‐speed centrifugal spinning are proposed. The flow of spinning solution in the different rotary nozzles is simulated based on the theoretical analysis. It can be found that the curved‐tube nozzle is better for high‐speed centrifugal spinning comparing with the velocity distribution of spinning solution in the four different spinning nozzles. The influence degree of the structure parameters of the curved‐tube nozzle on the solution outlet‐velocity is explored by orthogonal test method. The result shows that the curved‐tube nozzle with an inlet diameter of 10 mm, conical transition pipe length of 3 mm, nozzle outlet diameter of 0.8 mm, curvature radius of 4 mm, and central angle of curved tube of 30°, can effectively enhance the outlet velocity of spinning solution. Finally, it is proved by centrifugal spinning experiment that the curved‐tube nozzle after optimization can improve the morphology and quality of nanofibers. Abstract : High‐speed centrifugal spinning is a novel method to fabricate nanofiber by centrifugal force which is generated by high‐speed rotating nozzles. The spinning nozzles rotates at high speed when the motor is energized and the spinning solution in the container is ejected from the nozzle with the action of centrifugal force. The jet flow of spinning solution is stretched into nanofiber and eventually collected on the collection device.